Homologous pairing of single-stranded circular DNAs catalyzed by recA protein. - Keener, S L (1984)
RecA protein catalyzes annealing between pairs of circular single-stranded DNA molecules containing complementary sequences varying in length from 3550 nucleotides to 181 nucleotides. The reaction requires ATP and catalytic amounts of recA protein. Molecules containing large complementary inserts are annealed by recA protein to form large multimeric aggregates that migrate slowly in agarose gels. In contrast the products formed from circular molecules containing short complementary regions are principally dimeric structures. We have used electron microscopy, thermal denaturation and kinetic studies to analyze these reaction products. Our results indicate that recA protein catalyzes multiple nucleation events between complementary DNA sequences in the absence of a free end and when these sequences are flanked by extensive noncomplementary regions.